2021
DOI: 10.1016/j.rmed.2021.106504
|View full text |Cite
|
Sign up to set email alerts
|

The association between carotid-femoral pulse-wave velocity and lung function in the Swedish CArdioPulmonary bioImage study (SCAPIS) cohort

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Our finding that greater lung function was cross-sectionally associated with less stiff arteries largely supports previously published research. 17,[19][20][21][22]24,25 Bolton et al 19 function in later-life with lung function 20 years earlier at midlife in terms of associations with central arterial stiffness and concluded that lung function at mid-life was a better predictor of later-life arterial stiffness than measures of lung function later in life. 19 However, our findings suggest that lung function at mid-life and later-life were both associated with later-life arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our finding that greater lung function was cross-sectionally associated with less stiff arteries largely supports previously published research. 17,[19][20][21][22]24,25 Bolton et al 19 function in later-life with lung function 20 years earlier at midlife in terms of associations with central arterial stiffness and concluded that lung function at mid-life was a better predictor of later-life arterial stiffness than measures of lung function later in life. 19 However, our findings suggest that lung function at mid-life and later-life were both associated with later-life arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Most prior studies of lung function and arterial stiffness, as measured by pulse wave velocity (PWV), have been cross sectional, and support an inverse association between lung function and arterial stiffness. The majority of cross-sectional studies assessing expiratory function, measured by forced expiratory volume in one second (FEV 1 ), found poor expiratory function to be associated with greater arterial stiffness, [17][18][19][20][21][22] while some did not. 9,23 Other studies have assessed the cross-sectional association of lung capacity, measured by force vital capacity (FVC), and arterial stiffness, finding mixed results: some studies found poor lung capacity to be associated with stiffer arteries, 19,[21][22][23][24][25] while others did not.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carotid–femoral pulse wave velocity (PWV) was measured by trained biomedical scientists using an applanation tonometer according to a previously published protocol. 21 In brief, measurements were made twice using the SphygmoCor XCEL device (from Atcor Medical, Sydney, NSW, Australia). The average of these measurements was used for analysis, and calculated using a correction factor of 0.8 in accordance with current international guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…As for the sex differences, at least two studies ( 143 , 144 ) have shown that males in comparison to females have stiffer arteries, assessed by carotid-femoral pulse wave velocity (cfPWV), which could help to predict the loss of lung function in male subjects. The Swedish CArdioPulmonary bioImage Study (SCAPIS) ( 145 ) observed the reduction in PWV by 1-SD increase in Forced Expiratory Volume 1 sec (FEV1) and diffusing capacity for carbon monoxide only in males but not in females from healthy populations.…”
Section: Early Vascular Aging: Sex and Gendermentioning
confidence: 99%